Gelatin's Effect on Iron Oxide Nanoparticle Properties and Its Use in Thermal Regeneration for Methylene Blue Photodegradation - Ulfa, Maria; Poetry, Sabrina Devinta (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Two series of iron oxide nanoparticles with different textural and structural characteristics were synthesized using the sol-gel method. The iron oxide nanoparticles were made with synthetic (Pluronic P123 Amphiphilic Block Copolymer) and natural (gelatin) double templates and single P123 templates. The influences of the addition of the gelatin template on the microstructure, methylene blue degradation, and thermal photocatalyst regeneration were investigated. The X-ray Diffraction (XRD) examination revealed the formation of iron-P123-gelatin (iron oxide made with P123 and gelatin templates) and iron-P123 (iron oxide made with only P123 template) with hematite and maghemite phases, where the crystallinity and crystallite size increased due to the presence of gelatin. Fourier Transform Infra Red (FTIR) studies indicated a peak at 500 cm−1, revealing the iron groups in both samples and increased intensity in the hydroxyl and carbonyl groups due to gelatin. Furthermore, the surface area, pore volume, and pore diameter of iron-P123-gelatin exhibited an increment due to gelatin addition. According to the Thermogravimetric Analysis (TGA) and Differential Thermal Analyzer (DTA) data, the sample with gelatin had higher thermal stability and weight loss than that without gelatin. The photodegradation of methylene blue utilizing iron-P123-gelatin reached 91.5%, showing a better performance than that of iron-P123. Finally, iron-P123-gelatin demonstrated a promising photocatalyst thermal regeneration for methylene blue photodegradation for 5 cycles at various temperatures, and it is suggested that 450 °C was the ideal temperature. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).